Association between dietary selenium intake and endometriosis risk: a cross-sectional analysis - Guo, Jia-Jie; Li, Rui-Xuan; Shang, Wen-Li; Zheng, Ya-Fang; Zhu, Guo-Yi; Shu, Zhou-Chang; Liu, Gui-Chao; Ou, Hong-Biao; Li, Jia-Ying; Guo, Xu-Guang; Lin, Li-Hong (Frontiers in Endocrinology, 2025)
BackgroundEndometriosis (EMs) is a common chronic inflammatory disorder with estrogen dependency, and its causes and progression are not fully understood. With limited treatment options available, the dietary impact on EMs incidence has gained research interest. This study explores the link between dietary selenium intake and EMs risk, noting selenium’s key antioxidant role in reducing oxidative stress and inflammation, and its potential to modulate immune responses, offering protective effects.MethodsThe study included 39,352 participants from National Health and Nutrition Examination Survey (NHANES) data (1999-2006). We excluded individuals with missing data on dietary selenium intake or EMs status, pregnant women, and individuals with missing basic covariate data or suspected erroneous dietary selenium intake values. After these exclusions, a final cohort of 3,876 participants was included for detailed analysis. This cohort was stratified into two groups: 3566 individuals without a diagnosis of endometriosis and 310 individuals diagnosed with EMs. The relationship between EMs and dietary selenium intake was examined using a suite of statistical methodologies, including multivariate logistic regression to control for confounding variables, smooth curve fitting, threshold effect analysis and subgroup analysis.ResultsAfter adjusting for multiple covariates, the multivariate logistic regression model indicated a negative correlation between dietary selenium intake and the risk of developing EMs. In the highest dietary selenium intake group, the adjusted model II revealed a reduction in the risk of EMs by approximately 34.1% (OR = 0.659, 95% CI: 0.449, 0.967). The subgroup analysis revealed a negative relationship between quartiles of selenium intake and the risk of endometriosis in participants aged fifty years and older, in non-Hispanic white participants, in participants with PIR >=1.3 and <3.5, in participants with a high school education level or under, in participants who get married or live with a partner, in participants who have never drunk, and in participants who smoke currently.ConclusionsOur findings suggest a negative correlation between dietary selenium intake and endometriosis risk. However, potential confounding factors may influence this association. Given the limitations of this cross-sectional study, such as reliance on self-reported data, further prospective research is required to confirm causality and explore underlying mechanisms.